2007
DOI: 10.2105/ajph.2005.084848
|View full text |Cite
|
Sign up to set email alerts
|

Giving Everyone the Health of the Educated: An Examination of Whether Social Change Would Save More Lives Than Medical Advances

Abstract: Higher mortality rates among individuals with inadequate education reflect a complex causal pathway and the influence of confounding variables. Formidable efforts at social change would be necessary to eliminate disparities, but the changes would save more lives than would society's current heavy investment in medical advances. Spending large sums of money on such advances at the expense of social change may be jeopardizing public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(125 citation statements)
references
References 38 publications
0
122
0
3
Order By: Relevance
“…18 Woolf and coauthors estimated that giving all US adults the mortality rate of adults with some college education would save seven lives for every life saved by biomedical advances. 19 Stark racial or ethnic differences in education and income could largely explain the poorer health of blacks and some other minorities. The high school dropout rate is 18.3 percent among Hispanics, 9.9 percent among blacks, and 4.8 percent among non-Hispanic whites.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…18 Woolf and coauthors estimated that giving all US adults the mortality rate of adults with some college education would save seven lives for every life saved by biomedical advances. 19 Stark racial or ethnic differences in education and income could largely explain the poorer health of blacks and some other minorities. The high school dropout rate is 18.3 percent among Hispanics, 9.9 percent among blacks, and 4.8 percent among non-Hispanic whites.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…Some studies have found, for example, that academic disengagement is related closely to negative consequences, such as early student dropout, juvenile delinquency, and problem substance use (e.g., Henry, 2010;Henry, Knight, & Thornberry, 2012;Moretti, 2005;Rouse, 2005). The inequalities in achievements of minority ethnic students (Henry, et al, 2012;Woolf, Johnson, Phillips, & Philipsen, 2007), likewise, may be explained and accounted for by the feeling and experience of alienation. Some students may opt to adopt a criminal lifestyle, forging antisocial identity as a defence for their shortcomings and isolation.…”
Section: Consequences Of Belongingmentioning
confidence: 99%
“…De sterftedaling zou acht keer zo groot zijn, zo schatten de auteurs, als de daling die we met de medische zorg bereiken. 9 Ook voor Nederland zijn dit soort berekeningen gemaakt. Specifiek is dat bijvoorbeeld gedaan voor geletterdheid, een aspect dat samenhangt met opleiding, maar er zeker niet mee samenvalt.…”
Section: Maatschappelijke Invloeden Op De Volksgezondheidunclassified